External quality assessment schemes in bacteriology support public health in Germany—results from 2006 to 2023 - Lindenberg, Marc; Waldmann, Sabine; Suerbaum, Sebastian; Schlüter, Dirk; Ziesing, Stefan (Frontiers in Molecular Biosciences, 2024)
External Quality Assessment schemes (EQAS) are mandatory to ensure quality standards in diagnostic methods and achieve laboratory accreditation. As host institution for two German culturebased bacteriology EQAS (RV-A and RV-B), we investigated the obtained data of 590 up to 720 surveys per year in RV-A and 2151 up to 2929 in RV-B from 2006 to 2023. As educational instruments, they function to review applied methodology and are valuable to check for systemic-or method-dependent failures in microbiology diagnostics or guidelines. Especially, containment of multi-resistant bacteria in times of rising antibiotic resistance is one major point to assure public health. The correct identification and reporting of these strains is therefore of high importance to achieve this goal. Moreover, correct antibiotic susceptibility testing (AST) per se is important for selecting appropriate therapy, to restrict broad-spectrum antibiotics and minimize resistance development. The reports of participating laboratories displayed a high level of correct identification results in both schemes with mostly consistent failure rates around 2.2% (RV-A) and 3.9% (RV-B) on average. In contrast, results in AST revealed increasing failure rates upon modification of AST requirements concerning adherence to standards and subsequent bacterial species-specific evaluation. Stratification on these periods revealed in RV-A a moderate increase from 1.3% to 4.5%, while in RV-B failure rates reached 14% coming from 4.3% on average. Although not mandatory, subsequent AST evaluation and consistent reporting are areas of improvement to benefit public health.